2014
DOI: 10.1159/000357342
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Exercise in the Elderly

Abstract: Type 2 diabetes mellitus is highly prevalent among the elderly. Age-associated changes in body composition, obesity and sedentary behavior are some of the main factors responsible for the increased prevalence of diabetes in this population. Elderly patients experience important and specific issues, including the association of comorbidities and geriatric syndromes, use of many medications, the presence of dependencies and frailty. Physical activity has been shown to be as effective for the treatment of diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 39 publications
0
25
1
3
Order By: Relevance
“…Physical activity and exercise have been demonstrated to be beneficial for individuals with T2DM by optimally controlling metabolic risk factors for diabetes management [16, 17]. Exercise-mediated glucose metabolism improvement might be attributed to adiposity and insulin resistance reduction, although the effective strategy of exercise (e.g., to what extent) to regulate glycemic homeostasis in elderly diabetic patients remains largely unknown [1820]. The age-sensitive nature of HbA1c during ageing prompts the need to establish cutoff points of adiposity index for identifying the elderly population with abnormal glucose metabolism and other metabolic risks [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity and exercise have been demonstrated to be beneficial for individuals with T2DM by optimally controlling metabolic risk factors for diabetes management [16, 17]. Exercise-mediated glucose metabolism improvement might be attributed to adiposity and insulin resistance reduction, although the effective strategy of exercise (e.g., to what extent) to regulate glycemic homeostasis in elderly diabetic patients remains largely unknown [1820]. The age-sensitive nature of HbA1c during ageing prompts the need to establish cutoff points of adiposity index for identifying the elderly population with abnormal glucose metabolism and other metabolic risks [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of cardiovascular events has also been examined in a Cochrane systematic review of 11 trials, which concluded that the Mediterranean diet may modulate important cardiovascular risk factors (such as lower cholesterol and low-density lipoprotein), however meta-analysis was precluded by the vast 11 4 heterogeneity of the dietary interventions studied [20]; similar 11 5 conclusions have been drawn by non-Cochrane systematic JIG reviews (21]. Although it is likely that these data can be directly 117 extrapolated to people with NAFLD and metabolic syndrome, 118 there are no randomized trials examining the Mediterranean 119 diet's effect on clinically important liver related outcomes. A 120 small crossover trial (n = 12) in patients with biopsy proven 121 NAFLD of a Mediterranean diet for 6 weeks with crossover to 122 standard diet at 6 weeks, demonstrated reduced insulin resis- 123 tance and hepatic steatosis, independent of weight loss (22].…”
Section: Introductionmentioning
confidence: 99%
“…La actividad física ha demostrado ser tan eficaz para el tratamiento de la diabetes en los ancianos como en los pacientes más jóvenes, por lo que su práctica debe ser fuertemente alentada. La prescripción de ejercicios adaptados a las preferencias y limitaciones de cada paciente es altamente eficaz no sólo para el control glucémico, sino también para mejorar la independencia, la autoestima y la calidad de vida (15).…”
Section: Discussionunclassified
“…(2005), donde se demuestra un decremento significativo en el porcentaje de HbA1c, tal como se obtuvo en la presente investigación. En pacientes diabéticos se recomiendan los ejercicios aerobios, aunque actualmente el uso de los ejercicios de resistencia con pequeñas cargas no está contraindicado en los diabéticos no complicados (13,15,16). Las intervenciones estructuradas de la práctica de ejercicio, al menos durante 8 semanas, evidencia una disminución promedio de 0,66 % de los niveles de la Hb A1c en personas con DMT2 aun sin cambios significativos del índice de masa corporal (IMC) (7).…”
Section: Discussionunclassified